2020
DOI: 10.1080/26410397.2020.1749342
|View full text |Cite
|
Sign up to set email alerts
|

Exploring young women’s menstruation-related challenges in Uttar Pradesh, India, using the socio-ecological framework

Abstract: Menstruation frequently poses psychological, social, and health challenges for young women living in low-and middle-income countries. In countries such as India, where menstruation is stigmatised, it can be particularly difficult. This paper examines challenges related to menstruation for young women living in slums in Lucknow, Uttar Pradesh, India. The research was informed by the socio-ecological model. Life course interviews were conducted with 70 young women ages 15-24 living in the slums of Lucknow. Thema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 40 publications
5
33
0
Order By: Relevance
“…Poor access to water and sanitation facilities, lack of privacy, limited knowledge of menstrual hygiene practice [17], social stigma, and cultural restriction on activities [2] all inhibit the implementation of MHM at school. Menstruation poses a set of physical, socio-cultural, and economic challenges to adolescent girls that may interfere with their ability to attend a school or to participate in class fully [18].…”
Section: Introductionmentioning
confidence: 99%
“…Poor access to water and sanitation facilities, lack of privacy, limited knowledge of menstrual hygiene practice [17], social stigma, and cultural restriction on activities [2] all inhibit the implementation of MHM at school. Menstruation poses a set of physical, socio-cultural, and economic challenges to adolescent girls that may interfere with their ability to attend a school or to participate in class fully [18].…”
Section: Introductionmentioning
confidence: 99%
“…Toilets are dirt with doors broken. [ 27 ] A study showed only 42% changed their pads/clothes in the school due to the non-availability of dustbins and soaps. [ 26 28 ]…”
Section: Methodsmentioning
confidence: 99%
“…Women's and girls' choices about and control over their bodies have been constrained due to water and sanitation conditions. Specifically, women limited bathing, and washing hands, clothes, menstrual materials, and bathrooms; 62,72,84,86,109,130,151,183,184,186,188,215,218,267 restricted food and water to avoid defecation and urination; 121,154,160,165,170,178,198,210 suppressed defecation and urination urges; 2,48,167,170,174,176,177,200,203,215,221,222,224,227,233,234,236,256 delayed changing menstrual materials; 210,226,227,233,236 and took anti-diarrheal medicines 160 when lacking sufficient, safe or clean water and sanitation. Water improvements in E...…”
Section: A Bodily Integritymentioning
confidence: 99%
“…Multiple factors influence this ability, including conditions of water and sanitation facilities. Women and girls have described sanitation conditions as undesirable, dirty, disgusting, and nauseating 99,121,130,154,156,157,159,171,174,203,205,206,[208][209][210]212,213,215,[221][222][223]226,227,230,233,237 and lacking resources like disposal bins, soap, sufficient water, and buckets for washing or bathing, which are also needed during menstruation. 99,130,157,171,176,189,193,201,207,208,212,213,215,232,[238][239][240] Women used less preferred locations and sources for sanitation 116,156,159,…”
Section: A Bodily Integritymentioning
confidence: 99%